Body-movement-based human identification using convolutional neural network. (1st July 2018) - Batchuluun, Ganbayar; Naqvi, Rizwan Ali; Kim, Wan; Park, Kang Ryoung
Highlights: Our method is body movement-based human identification using front and back view. Our identification method is robust to the cases of people carrying items or with various poses. Deep learning method using thermal difference image-based three-channel inputs is used. Our collected database and trained CNN are public to other researchers. Abstract: Biometric technology based on human gait identifies humans at a far distance even if the individual's face is covered, hidden, or not visible to cameras in dark environments. Previous studies based on human gait were conducted considering both bright and dark environments for human identification in surveillance systems. The studies conducted in low-illumination environments (dark environments) are based on side view images (horizontal walking) of subjects. However, there are cases in which people only show the front and back views of their bodies while they are walking in low-illumination corridors. In these views, it is difficult to identify humans by using conventional features such as cycle, cadence, stride length of walking, and distance between points (ankle, knee, and hip). Additionally, the cases of problems such as people carrying cellphones and/or small personal items (a purse, bag, clothes, etc.) have critical effects on the accuracy of human identification. To overcome these problems, we propose a new human identification technique, which is based on the front and back view images of a human, captured by using a thermal camera sensor. Our technique uses movements of the human body for identification, particularly movement of the head, shoulders, and legs. We have used a convolutional neural network for feature extraction and classification in this study. Five datasets were compiled by collecting data of 80 people including men and women in both bright and dark environments. The experimental results with our collected data and open database showed a higher performance by using our method compared to those of previous studies.